Pelayanan Perbaikan Kualitas Air Bersih Sebagai Upaya Peningkatan Kesehatan Masyarakat di Wilayah Kerja Puskesmas Ngemplak II Sleman - Rois, Ibnu; Amalia, Rizki; Santjoko, Herman; Mutiara, Tintin (Jurnal Pengabdian Masyarakat - PIMAS, 2025)
The provision of clean and safe drinking water is a fundamental need to support public health. However, in some areas, poor groundwater quality, such as turbidity and high iron content, remains a major issue. This activity aims to address water quality problems in Kalurahan Umbulmartani Kapanewon Ngempak, Sleman Regency, through a community service program with a participatory approach. The activity involved the community in water treatment using a simple filter media consisting of fine sand, zeolite, gravel, and activated charcoal to reduce turbidity and iron levels in the water. The results show that this technique is effective in improving water quality and meeting health standards. Community empowerment through training, socialization, and direct assistance from cadres and related parties successfully enhanced community understanding of the importance of clean water and created positive changes in the independent management of clean water. Collaboration between the Puskesmas, village government, cadres, and local communities played a key role in the success of this program, which also contributed to efforts to prevent stunting in the area.